The Implementation of Emotion Recognition in Narrative Writing Learning in Primary School - Hudaa, Syihaabul; Zulhijra,; Maisaroh, Siti; Maghfiroh, Nasruliyah Hikmatul; Harsono,; Nisa', Titin Faridatun; Laksana, Sigit Dwi; Kuswandi, Iwan; Asmoni,; Mas'odi, (International Journal of Psychosocial Rehabilitation, 2020)
This article aims to illustrate the implementation of emotional ignition in writing narrative learning in elementary schools. This research uses descriptive research method that aims to describe the emotion ignition on learning of narrative writing. The research was conducted in SDN 4 Kediri. The results showed that Emotion ignition by using concrete objects media and film media is more getting a response from learners and show good results when compared to using media images.